2021
DOI: 10.3892/ol.2021.12913
|View full text |Cite
|
Sign up to set email alerts
|

Low LINC01272 predicts poor prognosis of non‑small cell lung cancer and its biological function in tumor cells by inhibiting miR‑1303

Abstract: Non-small cell lung cancer (NSCLC) is a malignant tumor associated with poor prognosis. The clinical value of long non-coding RNAs (lncRNAs) in the pathomechanism of various types of human malignancy has attracted increasing attention. The present study aimed to investigate the expression of LINC01272 in NSCLC and to determine its prognostic value and biological role. Tumor and adjacent non-tumor tissues from 108 patients with NSCLC and NSCLC cell lines were used in this study. The expression levels of LINC012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PELATON is a long intergenic nonprotein coding RNA1272 (also known as LINC01272 ). Few studies have indicated that it promotes cancer cell migration and invasion, such as gastric cancer ( 51 , 52 ), colorectal cancer ( 53 ), and non-small-cell lung cancer ( 54 ), but there is no report in GBM. PELATON showed significantly higher expression in GBM tissues and primary GBM cells, which were named PG-2, PG-3, PA-2, and PA-3 ( 42 ), and was mainly located in the plasma membrane of GBM cells ( Supplementary Figure 5A and Figures 5A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…PELATON is a long intergenic nonprotein coding RNA1272 (also known as LINC01272 ). Few studies have indicated that it promotes cancer cell migration and invasion, such as gastric cancer ( 51 , 52 ), colorectal cancer ( 53 ), and non-small-cell lung cancer ( 54 ), but there is no report in GBM. PELATON showed significantly higher expression in GBM tissues and primary GBM cells, which were named PG-2, PG-3, PA-2, and PA-3 ( 42 ), and was mainly located in the plasma membrane of GBM cells ( Supplementary Figure 5A and Figures 5A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in LINC01272 expression in tissues and cells of NSCLC patients may serve as an independent prognostic marker. LINC01272 overexpression may inhibit NSCLC cells proliferation, migration, and invasion by inhibiting MI-1303 [45]. LINC00261 downregulation in gastric cancer is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…And qRT-PCR indicated that only the change in miR-1303 was statistically significant. Though it has been reported that miR-1303 can mediate cellular proliferation in several cancers [ 26 31 ], miR-1303 has not been investigated in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%